THEORY OF ADMINISTRATIVE COERCION: CONCEPT AND CONTENTS - Бородін, Іван Лук’янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the analysis of measures of administrative coercion that are used in the activities of public authorities is relevant at the present stage of a legal, social state’s formation. In the process of constitutional rights and freedoms of a human and a citizen implementation, protection of public order and public safety, if it is necessary, the state has a right and a duty to apply certain restrictions of the rights and freedoms of subjects of public administration within the limits of the law. Therefore, bringing measures of coercion the state in line with the democratic, modern requirements and standards of civilized countries is today the priority task of legal science and practice. Methods: phenomenological; comparative-legal; sociological; logical; dialectical. Results: the suggested basic criteria for understanding the contents of administrative coercion as a legal phenomenon should serve the development of scientific thought in a given paradigm and become, to an appropriate extent, the basis for further development and improvement of administrative legislation that determines the legal personality of persons, participants of legal relations, in the process of administrative coercion application. Discussion: the issues of the contents of administrative coercion is carried out in the context of conceptually new views that determine the changes in the organizational-legal principles of the functioning of public administration bodies, creation of the necessary conditions for establishing relations between the subjects of public administration on the basis of partnership, improvement of methods and means of ensuring rights and freedoms of a human and a citizen, protection of public order and public safety.